Artificial redox enzymes - V. T. D. D`Souza (ՀՀ ԳԱԱ հրատ.)
A general method for synthesis of artificial redox enzymes has been offered. Some of the catalytic properties of these systems have been studied and presented.
Keywords: Biology; Biochemistry